An adsorptive stripping voltammetry of nickel and cobalt at a solid lead electrode. Issue 13 (20th October 2016) - Gęca, Iwona; Ochab, Mateusz; Korolczuk, Mieczyslaw
ABSTRACT: For the first time, a solid lead electrode (PbE) was exploited for adsorptive stripping voltammetric determination of Ni(II) and Co(II) in the presence of nioxime as a complexing agent. The calibration graphs for Ni(II) and Co(II) were linear from 0.059 to 0.59 µg L −1 and from 0.029 to 0.29 µg L −1 (accumulation time 120 s), respectively. The analytical parameters such as the detection limit and separation of analytical signals obtained at the solid lead electrode were comparable with those obtained using a lead film electrode while better in comparison to those reported before for the bismuth film or solid bismuth electrodes. Co(II) could be determined in the presence of a large excess of Ni(II) and Zn(II). The proposed electrode was applied to determine Co(II) and Ni(II) traces in certified reference material and a natural water sample with satisfactory results.